Yersinia pseudotuberculosis growth arrest during type-III secretion system expression is associated with altered ribosomal protein expression and decreased gentamicin susceptibility. - Justin Greene; Katherine L Cotten; Rhett A Snyder; Ryan C Huiszoon; Sangwook Chu; Rezia Era D Braza; Ashley A Chapin; Justin M Stine; William E Bentley; Reza Ghodssi; Kimberly M Davis (PLoS Pathogens)
It has been long appreciated that expression of the Yersinia type-III secretion system (T3SS) in culture is associated with growth arrest. Here we sought to understand whether T3SS expression is sufficient to trigger loss of exponential phase markers, and utilized a fluorescent reporter for ribosomal protein expression to detect changes in bacterial growth state. Using a fluorescent transcriptional reporter with the rpsJ/S10 promoter fused to a destabilized gfp variant, we confirmed reporter expression significantly increases in exponential phase and decreases as cells transition to stationary phase. In a mouse model of systemic Y. pseudotuberculosis infection, we found multiple subsets of bacterial cells in the mouse spleen, including cells with high T3SS and low S10 expression and cells with high expression of both markers. In bacterial media, growth inhibition with T3SS induction and a reduction in S10 expression were observed, but a significant proportion of cells retained high expression of both T3SS and S10. Paradoxically, while loss of T3SS expression rescued growth, lower S10 expression was detected, again indicating bacteria can express both markers simultaneously. In media, bacteria grow planktonically as individual cells, while in mouse tissues, bacteria form clustered extracellular communities. We utilized droplet-based microfluidics to encapsulate bacteria in spherical agarose droplets and model clustered growth, and observed high expression of T3SS without an impact on S10 levels. Finally, we show that T3SS expression is sufficient to promote antibiotic tolerance, but surviving bacteria in a gentamicin treatment mouse model specifically express low S10. Collectively, these data indicate that the growth arrest associated with T3SS induction can reduce antibiotic susceptibility, but cells surviving antibiotic treatment display lower levels of the exponential phase marker, S10.